2015
DOI: 10.1016/j.immuni.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Nuclear Receptor ERRα Controls Macrophage Metabolic Signaling and A20 Expression to Negatively Regulate TLR-Induced Inflammation

Abstract: The orphan nuclear receptor estrogen-related receptor α (ERRα; NR3B1) is a key metabolic regulator, but its function in regulating inflammation remains largely unknown. Here, we demonstrate that ERRα negatively regulates Toll-like receptor (TLR)-induced inflammation by promoting Tnfaip3 transcription and fine-tuning of metabolic reprogramming in macrophages. ERRα-deficient (Esrra(-/-)) mice showed increased susceptibility to endotoxin-induced septic shock, leading to more severe pro-inflammatory responses than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 49 publications
5
111
0
2
Order By: Relevance
“…ERRα transcriptionally regulates the expression of genes encoding energy metabolism regulators (28,30,31). To test whether ERRα could functionally phenocopy the role of MYC in mitochondrial respiration in osteoclasts, we measured mitochondrial respiration following RANKL stimulation using ERRα-deficient OCPs isolated from ERRα-null mice.…”
Section: Resultsmentioning
confidence: 99%
“…ERRα transcriptionally regulates the expression of genes encoding energy metabolism regulators (28,30,31). To test whether ERRα could functionally phenocopy the role of MYC in mitochondrial respiration in osteoclasts, we measured mitochondrial respiration following RANKL stimulation using ERRα-deficient OCPs isolated from ERRα-null mice.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblotting was performed as described previously (22). For immunoblotting, cells were lysed in RIPA (10 mM Tris-HCl at pH 8, 1 mM EDTA, 140 mM NaCl, 0.1% SDS, 0.1% sodium deoxycholate, and 1% Triton X-100) and a protease inhibitor mixture (Roche).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Briefly, total RNA from cells was isolated using TRIzol reagent (15596-026; Thermo Fisher Scientific) and used for synthesis of cDNA with Superscript II reverse transcriptase (Invitrogen). For semiquantitative RT-PCR reactions involved 30 cycles of annealing, extension, and denaturation as described previously (22). Reactions were run on a Veriti 96-Well Thermal Cycler (Thermo Fisher).…”
Section: Immunoblottingmentioning
confidence: 99%
“…A recent interesting finding concerns a connection between the orphan nuclear receptor ERRα and a critical negative regulator of inflammation, the deubiquitinating enzyme A20 (Yuk et al, 2015). ERRα is a well-known regulator of energy metabolism and mitochondrial biogenesis (Villena and Kralli, 2008).…”
Section: Negative Control Of Metabolic Reprogramming In M1 Macrophagementioning
confidence: 99%
“…A20 has been shown to be a key inhibitor of inflammation in multiple human diseases, recent notable examples being to prevent rheumatoid arthritis and also asthma (Vande Walle et al, 2014;Schuijs et al, 2015). Yuk et al (2015) have shown that ERRα directly binds to the A20 gene promoter and increases its expression. ERRα-deficient mice are highly susceptible to LPS-induced septic shock and also have elevated glycolysis and decreased oxidative phosphorylation.…”
Section: Negative Control Of Metabolic Reprogramming In M1 Macrophagementioning
confidence: 99%